2015
DOI: 10.1002/ptr.5317
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Anthraquinones: Differential Effects of Rumex Seed Extracts on Rat Organ Weights and Biochemical and Haematological Parameters

Abstract: The genus Rumex and related species such as Rheum and Polygonum are widely used as medicinal herbs and foods. They contain anthraquinones (AQ) such as emodin and chrysophanol as active ingredients, and there is concern about the toxicity of these compounds. This study evaluated the chronic effects of Rumex patientia seed aqueous and ethanolic extracts, in male and female rats separately, on organ weights and over 30 haematological, biochemical and histological parameters, immediately after 14-week administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Ethanol solution extracts of R . patientia , which contain anthraquinones, such as emodin and chrysophanol, as active ingredients, caused irreversible pathological changes at very high doses (4000 mg/kg), although lower doses and aqueous extracts produced either non‐significant or reversible changes (Islam et al ., ). Therefore, long‐term administration of high doses of anthraquinones extracts should be avoided altogether during pregnancy.…”
Section: Toxicitymentioning
confidence: 97%
“…Ethanol solution extracts of R . patientia , which contain anthraquinones, such as emodin and chrysophanol, as active ingredients, caused irreversible pathological changes at very high doses (4000 mg/kg), although lower doses and aqueous extracts produced either non‐significant or reversible changes (Islam et al ., ). Therefore, long‐term administration of high doses of anthraquinones extracts should be avoided altogether during pregnancy.…”
Section: Toxicitymentioning
confidence: 97%
“…The natural origin of molecules, in this case quinones, does not guarantee that they are harmless. Indeed, some natural quinones, such as anthraquinones from Rumex patientia that are used in the pharmaceutical and food industries, can cause pathological effects in vivo if used at high doses (≥ 4000 mg/kg), whereas lower doses produce slight or nonsignificant effects [88]. One report on the toxicity of various natural anthraquinones indicated a potential health and genotoxic effect on animals and humans if these quinones, and especially their aglycones, are directly ingested into the body in large quantity (≥ 1000 mg/kg) for a longer period (at least 2 weeks), despite their low bioavailability (< 0.1) [89] Nevertheless, when compared with synthetic anthraquinone or azo dyes, the natural substances are less harmful.…”
Section: Toxicity Of Natural Quinonesmentioning
confidence: 99%
“…In addition to the FDA-approved drug, boceprevir here we observed that the anthraquinones, particularly alterporriol Q possess significant inhibitory potential towards SARS-CoV-2 M pro . Naturally occurring anthraquinones have low toxicity and different biological activities (Chien et al 2015 ; Islam et al 2015 ). Therefore, these observations indicate promising potential for the use of natural anthraquinones for the treatment of COVID-19.…”
Section: Resultsmentioning
confidence: 99%